2002
DOI: 10.1046/j.1365-2672.2002.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clavibacter michiganensis subsp. sepedonicus by AmpliDet RNA, a new technology based on real time monitoring of NASBA amplicons with a molecular beacon

Abstract: Aims: To develop a procedure for direct detection of viable cells of Clavibacter michiganensis subsp. sepedonicus (Cms), the causal organism of bacterial ring rot in potato, based on AmpliDet RNA TM , in which amplicons generated by nucleic acid sequence based amplification (NASBA) are monitored in real time with a molecular beacon. Methods and Results: Five methods were evaluated and fine-tuned for extraction of RNA from Cms. The most efficient non-commercial RNA extraction method included an enzymatic breakd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…In addition, they may amplify the DNA of closely related species and even the DNA of other nonpathogenic soil bacteria (Van der Wolf et al 2005). Other techniques developed for C. michiganensis identification include fluorescent in situ hybridization (FISH) (Van Beuningen et al 1995), real-time PCR (Schaad et al 1999;Bach et al 2003), and nucleic acid sequence based amplification (NASBA) (Van Beckhoven et al 2002). The methods that are applied to differentiate C. michiganensis species are restriction fragment length polymorphisms (RFLP) analysis of the amplified internal transcribed spacer (ITS) between 16S and 23S rRNA genes region of the rrn operon (Lee et al 1997a;b;Borowicz 2001) and rep-PCR (Louws et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they may amplify the DNA of closely related species and even the DNA of other nonpathogenic soil bacteria (Van der Wolf et al 2005). Other techniques developed for C. michiganensis identification include fluorescent in situ hybridization (FISH) (Van Beuningen et al 1995), real-time PCR (Schaad et al 1999;Bach et al 2003), and nucleic acid sequence based amplification (NASBA) (Van Beckhoven et al 2002). The methods that are applied to differentiate C. michiganensis species are restriction fragment length polymorphisms (RFLP) analysis of the amplified internal transcribed spacer (ITS) between 16S and 23S rRNA genes region of the rrn operon (Lee et al 1997a;b;Borowicz 2001) and rep-PCR (Louws et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The isolates must be identified by serology, bioassay and a set of conventional nutritional and physiological tests (Jansen and Van Vaerenbergh, 1987). Since the whole procedure is time consuming, different detection and identification methods based on molecular techniques have been proposed to speed up the process (De Boer et al, 1995;Li et al, 1997;Louws et al, 1998;Wullings et al, 1998;Pastrik and Rainey, 1999;Pastrik, 2000;Palomo et al, 2000;Smith et al, 2001;Beckhoven et al, 2002;Rivas et al, 2002;Fessehaie et al, 2003). Moreover, the European Union has supported a project (DIAGPRO) for the standardization and validation of a protocol to detect and diagnose this quarantine bacterium (available in www.csl.gov.uk/science/organ/ph/diagpro).…”
mentioning
confidence: 99%
“…The oligonucleotides used in this study are shown in Table 1. Primers Af2 and Ar and molecular beacon MB CMS1 (specific sequence) were previously designed and tested by van Beckhoven et al (24) and modified as indicated in Table 1. M. avium subsp.…”
Section: Methodsmentioning
confidence: 99%